DINAMIKA PERKAWINAN ADAT BALI - Kadek Hemamalini; Untung Suhardi (DHARMASMRTI: Jurnal Ilmu Agama dan Kebudayaan, 2015)
It is found based on the research that ‘sentana rajeg’ has become the term to be the problem solver within the wedding system in Bali. This term is obviously based on the teaching of Hinduism in Rg. Veda. The sentana rajeg is caused to be effective in accordance with the Hindu script of law, Manawadharmasastra IX.127-140. Considering the Balinese traditional regulation, the condition of sentana rajeg has given an opportunity for the position of the anak sentana to be legalized through the traditional process in a sentana institution because of the philosophical values and the teaching of Hinduism embedded within. One of its functions is that the sentana rajeg may be used to avoid the revocation of right called camput as well as to maintain the traditional obligations, ayahan, on the parahyangan, the pawongan, and the pawongan.